Recurrent Warscape in Beirut public spaces: forty years later (1975-2015) - Hindi, Nadine (International Planning History Society Proceedings, 2016)
In the context of a tormented Middle East geopolitics and the ongoing Arabo-Israeli conflict, a civil war erupted in Lebanon in 1975 and went uninterrupted for fifteen long years. As early as the first two-years-round of civil war in 1975-77, violent armed conflict manifested itself in an urban nature and contextualized in the capital Beirut. Back then, the civil war targeted systematically the public spaces and achieved purposefully the dual objective of mutating social practice and mutilating their urban form into a geography of fear. Intriguingly, during the unreconciled civil war aftermath, the display of instability and conflict kept on marking sporadically the same public spaces at different incidents. Three decades following the eruption of urban violence in 1975, intermittent events of social and political nature took place between 2005 and 2015, triggered by the assassination of the prime minister. This paper will tackle the two case studies of public spaces which are the pivots of the recurrent warscape: Place des Martyrs and the seaside hotels’ area, both symbols of social and geographic contestations at simultaneous times of peace and war. Based on an interdisciplinary literature, the socio political manifestations will be highlighted by unfolding them across time and space. Signs of discontentment and instability are manifested under different facets and patterns varying from passive intangible representations to active outbursts. The perpetuation of events hitherto occurring in the same urban spaces will be studied from the perspective of the social and political realities. In the absence of a mono-causal factor for warscape recurrence, mapping conflict in the urban space is a suggested tool to approach the perpetuation issue from a context-specific perspective. It is as well an opportunity to raise the question on the relation between the socio-political claims and their reverberation in the same urban spaces.